If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ax + box = -1c Reorder the terms: box + xA = -1c Solving box + xA = -1c Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1xA' to each side of the equation. box + xA + -1xA = -1c + -1xA Combine like terms: xA + -1xA = 0 box + 0 = -1c + -1xA box = -1c + -1xA Divide each side by 'ox'. b = -1co-1x-1 + -1o-1A Simplifying b = -1co-1x-1 + -1o-1A
| 1x+4x=32 | | 8x-6+5=7 | | 4t+9=-8t+-13 | | 3(x-1)+3=4x-1 | | 7(c-7)+4c=-29(c+5) | | 8t-9=6t-3 | | 2x-7y=27 | | 0=15c^2-22c-5 | | 2x^2+-6x+9=0 | | 1.5s=4s-21 | | -2.5y+2=-1.5y-4 | | 5p+9=2p-1 | | Y=1.1*25+157 | | f=-2+4x+-2x^2 | | 2+x=2-2x | | 60(t-2)=30r | | -7x+3-9x= | | 85+(2x-5)= | | -3.4w=-22.1 | | 2=8(t)-4.9(t) | | 7x-[x-(2x+8)]=3x-7 | | 6x=9x-15 | | 2=8(t)-4.9(t)2 | | 3x+4y+6z=100 | | Y=1.1*40+157 | | 0.5a+(a-1)-(0.2a+10)=0.2a-(0.2a-28) | | 4x-7=6(x-3) | | 7(-6x+8)=-322 | | 1x-4=5 | | -30y+110=-12y+70 | | 0.5D-5=6 | | 55+(x+25)= |